DOCUMENTARY FILM DIRTY VOTE: SUBSTANCE AND SENSATION - Maryam Salampessy; Ade Risna Sari; Muhamad Irfan Florid; Widyastuti; Andro Ruben Runtu (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Recently, the documentary film "Dirty Vote" succeeded in shaking up the world of politics in Indonesia and dividing parties into two camps. One camp believes that the film is an instrument or medium to create intelligent voters and is a form of dissatisfaction with the Constitutional Court's decision which gave Gibran Rakabuming Raka the opportunity to become a Vice Presidential Candidate. However, on the other hand, a number of groups believe that the film is only looking for sensation and there is no scientific analysis that is in line with systematic methodology in scientific research. Based on this, this research aims to analyze the documentary film "Dirty Vote" which functions as substance or just sensation. This research is qualitative research with a descriptive approach which aims to reveal the purpose/purpose of the presence of documentary films as substance or mere sensation. The data used in this research is secondary data that researchers obtained from scientific manuscripts, books, trusted websites, and so on which are commonly used in every research. This data is analyzed using the SWOT method with the standard that if there are many strengths and opportunities it leads to substance and if there are many weaknesses and challenges it leads to sensation.